New record of Orientus ishidae (Matsumura, 1902) (Hemiptera: Cicadellidae) in Bulgaria with notes on the distribution of Acanalonia conica (Say, 1830) (Hemiptera: Acanaloniidae) - Ilia Gjonov; Tsvetomir Tsvetanov; Radost Angelova (Historia naturalis bulgarica)
Orientus ishidae (Matsumura, 1902), a leafhopper species native to East Asia, has been increasingly reported in Europe due to its potential role as a vector of phytoplasmas affecting agricultural crops. In this study, we present the first confirmed record of O. ishidae in Bulgaria, collected from Varna town during field surveys in 2024. The occurrence of O. ishidae in Bulgaria raises concerns about its potential impact on the country’s agriculture, particularly grapevines and fruit crops, which are vulnerable to the phytoplasma diseases vectored by this species. A new distribution records of Acanalonia conica (Say, 1830), previously known only from the most southeastern parts of the country, is indicating that the species established in the north-east and west parts. These records expand the known distribution of both species, O. ishidae and A. conica in Europe, highlighting the need for continued monitoring and management strategies.